The Effect of Individual Characteristics, Organizational Support, and Work Environment on Job Satisfaction among Medical Personnel at Pangeran Jaya Sumitra Regional Gen-eral Hospital, Kotabaru - Frisna Sihombing; Juanita Juanita; Destanul Aulia (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Job satisfaction is a key consideration for employees to remain with a company. Employees consider both internal and external satisfaction. Factors that can increase job satisfaction are individual characters, organizational support and work environment. The purpose of this study is to analyze the influence of individual characteristics, organizational support, and the work environment on job satisfaction. The researcher used a quantitative approach through the distribution of questionnaires and hospital data to 50 medical workers. The study findings show that individual characteristics do not significantly influence medical job satisfaction. Age, gender, education, employment status, length of service, and marital status did not significantly influence the results, with p-values > 0.05. Meanwhile, organizational support and work environment significantly influence the job satisfaction of medical workers at Pangeran Jaya Sumitra Hospital, Kotabaru. Superior support, reward support, and fairness support all showed significant effects, with p-values < 0.05. Similar results were found in the physical work environment and non-physical work environment, with a p-value <0.05. Therefore, based on this view, it can be concluded that hospitals need to pay attention to organizational support and the work environment in order to create a sense of satisfaction while working.